Vibrational Spectroscopic Characterization and Coherent Anti-Stokes Raman Spectroscopy (CARS) Imaging of Artepillin C. Issue 7 (July 2020) - Pazin, Wallance M.; Furini, Leonardo N.; Solovyeva, Vita; Lemma, Tibebe; Rubira, Rafael J. G.; Jørgensen, Bjarke; Constantino, Carlos J. L.; Brewer, Jonathan R.
In the following work, the vibrational spectroscopic characteristics of artepillin C are reported by means of Fourier transform infrared (FT-IR) and Raman spectroscopies, surface-enhanced Raman scattering (SERS), and coherent anti-Stokes Raman scattering (CARS) microscopy. Artepillin C is an interesting compound due to its pharmacological properties, including antitumor activity. It is found as the major component of Brazilian green propolis, a resinous mixture produced by bees to protect their hives against intruders. Vibrational spectroscopic techniques have shown a strong peak at 1599 cm −1, assigned to C=C stretching vibrations from the aromatic ring of artepillin C. From these data, direct visualization of artepillin C could be assessed by means of CARS microscopy, showing differences in the film hydration obtained for its neutral and deprotonated states. Raman-based methods show potential to visualize the uptake and action of artepillin C in biological systems, triggering its interaction with biological systems that are needed to understand its mechanism of action.